Hydrology of the Glenn Creek Watershed Tanana River Basin, Central Alaska - Dingman,S. Lawrence (1971)
The results of a four-summer (1964-1967) hydrologic study of the watershed of Glenn Creek, about 8 miles north of Fairbanks, Alaska, in the Yukon-Tanana uplands physiographic province, are presented. This work was initiated to provide initial base line hydrologic data for a small subartic watershed, the first of its kind in North America. Standard hydrologic and meteorologic instrumentation was used, and streamflow characteristics were analyzed by standard hydrograph-analysis techniques. The stream is second-order, and drains an area of 0.70 square mile. Basin elevations are from 842 ft to 1618 ft. In regard to topography, geology, soils, permafrost, vegetation, and climate, the watershed seems to be representative of low-order, low-elevation about half the 12.3-in. normal annual precipitation is runoff. The remainder is the actual evapotranspiration, which equals only about 30% of estimated potential evapotranspiration. For individual storms, runoff/rainfall proportions were from 0.03 to 4.2, and were positively correlated with antecedent discharge of the stream, which is a measure of watershed wetness. (Author)